2016
DOI: 10.1038/srep28936
|View full text |Cite
|
Sign up to set email alerts
|

Band-like transport in highly crystalline graphene films from defective graphene oxides

Abstract: The electrical transport property of the reduced graphene oxide (rGO) thin-films synthesized from defective GO through thermal treatment in a reactive ethanol environment at high temperature above 1000 °C shows a band-like transport with small thermal activation energy (Ea~10 meV) that occurs during high carrier mobility (~210 cm2/Vs). Electrical and structural analysis using X-ray absorption fine structure, the valence band photo-electron, Raman spectra and transmission electron microscopy indicate that a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 39 publications
2
67
0
Order By: Relevance
“…Presumably, in conducting domains, the subsequent annealing of a RGO sample removes defects and increases carrier concentrations [10−12]. Previously, it has been observed that the annealing of the RGO can lead to a Fermi level shift in the disordered graphitic sample due to generation of additional carriers [54,55]. Therefore, we can apply equation (6) in this case as well which can explain the ∆Σ ∝−∆n eff 0.5 behavior in the conducting domains of the RGO.…”
Section: Mmentioning
confidence: 99%
“…Presumably, in conducting domains, the subsequent annealing of a RGO sample removes defects and increases carrier concentrations [10−12]. Previously, it has been observed that the annealing of the RGO can lead to a Fermi level shift in the disordered graphitic sample due to generation of additional carriers [54,55]. Therefore, we can apply equation (6) in this case as well which can explain the ∆Σ ∝−∆n eff 0.5 behavior in the conducting domains of the RGO.…”
Section: Mmentioning
confidence: 99%
“…11,24,25) Theoretical calculation indicates that the work function of the rGO with an oxygen concentration in the 10-20% range can be tunable between 5.0-5.5 eV. 26) For example, the calculated work function of the hydroxyl group (5.0-5.3 eV) is higher than that of graphene (4.2 eV).…”
Section: Methodsmentioning
confidence: 99%
“…5(a) and 5(b). From the transmission electron microscopy observations in a previous study, 11) we found that such defects as vacancies and amorphous-like π networks composed of a mixture of sp 2 and sp 3 structures remain in the rGO films prepared by a low process temperature below 900°C. The amorphous-like π networks have a larger work function (4.9-5.0 eV) 32) than graphite or graphene.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations